Frontispiece: Capture of CO2 by a Cationic Nickel(I) Complex in the Gas Phase and Characterization of the Bound, Activated CO2 Molecule by Cryogenic Ion Vibrational Predissociation Spectroscopy. Issue 4 (18th January 2016) - Menges, Fabian S.; Craig, Stephanie M.; Tötsch, Niklas; Bloomfield, Aaron; Ghosh, Subrata; Krüger, Hans‐Jörg; Johnson, Mark A.
Abstract : CO 2 Activation The activation of CO2 by a cationic mononuclear nickel(I) complex is described by M. A. Johnson et al. in their Communication onpage 1282 ff. The resulting complex features a bent CO2 molecule (148°) bound to the metal center in an η 2 arrangement.